2013
DOI: 10.1016/j.jse.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Age-related degenerative functional, radiographic, and histological changes of the shoulder in nonhuman primates

Abstract: Background Non-human primates have similar shoulder anatomy and physiology compared to humans and may represent a previously underutilized model for shoulder research. This study sought to identify naturally occurring bony and muscular degeneration in the shoulder of non-human primates and to assess relationships between structural and functional aspects of the shoulder and measures of physical function of the animals. We hypothesized that age-related degenerative changes in the shoulders of non-human primates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 54 publications
2
33
0
1
Order By: Relevance
“…Walch et al [24] showed that increasing age was associated with increased glenoid retroversion in patients with primary glenohumeral arthritis. Similar results have also been found in studies of non-human primates [19]. However, it is possible that in patients where the arthritis has progressed to the point of needing a shoulder arthroplasty, age no longer predicts the amount of glenoid wear, and by extension the need for glenoid resurfacing.…”
Section: Discussionsupporting
confidence: 78%
“…Walch et al [24] showed that increasing age was associated with increased glenoid retroversion in patients with primary glenohumeral arthritis. Similar results have also been found in studies of non-human primates [19]. However, it is possible that in patients where the arthritis has progressed to the point of needing a shoulder arthroplasty, age no longer predicts the amount of glenoid wear, and by extension the need for glenoid resurfacing.…”
Section: Discussionsupporting
confidence: 78%
“…Reductions in muscle fiber force in the vastus lateralis were present in older vervets, 7 although it is unclear if the upper extremity musculature experiences the same decline. Older vervets demonstrated age-related deteriorations of the shoulder similar to reports in older adult humans including; degeneration of the glenoid, increased glenoid retroversion, and decreased supraspinatus superficial cross-sectional area.. 31 Similarly, measures of physical performance that incorporate the upper extremity were diminished in older vervets. 7,31,39 However, within this vervet species, age-related changes to the upper extremity musculature have not been evaluated and degenerative rotator cuff tears, a common age-related injury affecting older adult humans, 44 have not been described.…”
Section: Introductionsupporting
confidence: 59%
“…An animal model of upper extremity aging would more easily allow for longitudinal studies by limiting many of the logistical concerns associated with human subjects. Unfortunately, data regarding musculoskeletal degeneration in animals resulting strictly from normal aging are limited 7,12,24,31,32 and many of the animal models are small, quadrupedal, or have bony geometry that is substantially different from that of a human. 9,22,31 A non-human primate model may offer a solution that mitigates many of these problems.…”
Section: Introductionmentioning
confidence: 99%
“…Although experimental models of disease do exist, 85 a major advantage of these species is the development of naturally occurring OA in multiple joints that very closely mimics the onset and progression seen in aging humans. 23,24,55,86,120 Disease severity and age are closely correlated in this model, but the spectrum of disease across ages mimics that seen in humans, with some younger animals affected with moderate disease (particularly young males) and some elderly individuals spared entirely. 55,86 Although the joint biomechanics of nonhuman primates do differ from humans, they are more similar than those of strict quadrupeds.…”
mentioning
confidence: 82%